2016
DOI: 10.1080/13696998.2016.1223680
|View full text |Cite
|
Sign up to set email alerts
|

Burden of illness for super-refractory status epilepticus patients

Abstract: SRSE is associated with high mortality and morbidity, which place a high burden on healthcare resources. Projections based upon the findings of this study suggest an estimated 25,821-41,959 cases of SRSE may occur in the US each year, but more in-depth studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 50 publications
13
35
0
1
Order By: Relevance
“…A recent retrospective study from the United States on a pediatric SRSE patient population is in line with our results with an average LOS for children aged 0‐18 of 20 days and an average ICU stay of 12 days . Mean hospital cost amounted to USD 73 230 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A recent retrospective study from the United States on a pediatric SRSE patient population is in line with our results with an average LOS for children aged 0‐18 of 20 days and an average ICU stay of 12 days . Mean hospital cost amounted to USD 73 230 .…”
Section: Discussionsupporting
confidence: 89%
“…The observed database incidence rate of 17.6 cases per 100 000 patients is generally in alignment with numerous previous reports in various pediatric populations . The most recent comprehensive studies showed pediatric SE incidences of 13‐23 per 100 000 children .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…SE is refractory to adequate first‐ and second‐line treatment with benzodiazepines (BZDs) and nonsedating antiseizure drugs (ASDs) in 31%‐44% of cases . Refractory status epilepticus (RSE) is associated with higher morbidity and mortality than SE that responds to initial treatment, contributing to increased health care costs . Because RSE becomes more refractory to treatment over time, current management guidelines, based on expert opinion, suggest that the duration of an artificially induced (therapeutic) coma (TC) should last between 24 and 48 hours .…”
Section: Introductionmentioning
confidence: 99%